2023
DOI: 10.3390/life13040889
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for Severe COVID-19 Infection and Multisystem Inflammatory Syndrome in Adults and Children

Abstract: Coronavirus disease 2019 (COVID-19) rapidly emerged as a global pandemic, placing imminent stress and burden on healthcare resources and workers worldwide. Many patients who present with a severe COVID-19 infection are at high risk of developing severe acute respiratory distress syndrome (ARDS), leading to a vast number of patients requiring mechanical ventilation and a high mortality rate. Similar to Middle East respiratory syndrome, COVID-19 demonstrates an initial viral replication phase that manifests as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Moreover, the common gastrointestinal involvement observed in MIS-C is less frequent in Kawasaki disease-affected children [11,13,[24][25][26]29,33,34,40]. Furthermore, it is noteworthy that MIS-C results from an abnormal immune response to acute SARS-CoV-2, supporting the current view of its post-infectious nature [13,16,24,34,41,42]. Even if the MIS-C pathogenic mechanism is still unknown, it is strongly supposed to be an autoimmune vasculitis, in which higher anti-SARS-CoV-2 IgG antibodies are associated with a cytokine storm characterized by increased levels of pro-inflammatory cytokines (i.e., TNFα, IL1β, IL6, IL8, IL18) and with increased coronary disease biomarkers, thus resulting in diffuse endothelial damage through immune complexes and complement pathways' activation.…”
Section: Multisystem Inflammatory Syndrome In Children (Mis-c)mentioning
confidence: 61%
See 3 more Smart Citations
“…Moreover, the common gastrointestinal involvement observed in MIS-C is less frequent in Kawasaki disease-affected children [11,13,[24][25][26]29,33,34,40]. Furthermore, it is noteworthy that MIS-C results from an abnormal immune response to acute SARS-CoV-2, supporting the current view of its post-infectious nature [13,16,24,34,41,42]. Even if the MIS-C pathogenic mechanism is still unknown, it is strongly supposed to be an autoimmune vasculitis, in which higher anti-SARS-CoV-2 IgG antibodies are associated with a cytokine storm characterized by increased levels of pro-inflammatory cytokines (i.e., TNFα, IL1β, IL6, IL8, IL18) and with increased coronary disease biomarkers, thus resulting in diffuse endothelial damage through immune complexes and complement pathways' activation.…”
Section: Multisystem Inflammatory Syndrome In Children (Mis-c)mentioning
confidence: 61%
“…To date, there is mounting evidence that a small minority of children infected with SARS-CoV-2 later develop MIS-C, especially in those regions where the COVID-19 burden was higher [16,19,21,22]. According to the CDC diagnostic criteria, MIS-C patients are younger than 21 years, present with fever and laboratory evidence of multisystem involvement (two or more domains involved), and need hospitalization in the absence of an alternative diagnosis.…”
Section: Multisystem Inflammatory Syndrome In Children (Mis-c)mentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that, with regard to glucocorticoids, it was common for Japanese pediatricians/physicians to continue at the same (or higher) dose when treating COVID-19 cases ( Table 3 ). On the other hand, the biologic tocilizumab is not only used for PRD treatment but also for COVID-19 treatment [ 33 ]. It was recently suggested that the Janus kinase (JAK) inhibitor baricitinib may be effective for COVID-19 treatment [ 34 ].…”
Section: Discussionmentioning
confidence: 99%